Network evolution in the context of the global information infrastructure. - Lu, Hui-Lan (IEEE Communications magazine)
This article describes network evolution in the context of the global information infrastructure (GII), taking into consideration social and regulatory environments. It provides a GIIs vision for the evolution of wireless networks, which relies on the intelligent network (IN) to support the global and seamless introduction of services. It examines issues related to the Internet (e.g., resources, QoS, and security), which must be addressed properly before the Internet can be considered as the paradigm for the GII. In addition, this article discusses the software aspect of network evolution, equally applicable to all network paradigms. It focuses on the emergence of full network operating systems, which should transform networks into integrated programmable platforms supporting the development and execution of a wide range of services. Finally, this article suggests cooperation in standards definition among all players to effectively answer the technological challenges of future networks and provide both fair competition and regulated liberalization. The standardization of emerging network capabilities encompassing broadband, wireless/mobility, the Internet, and ultimately the GII, is presently ongoing in the ITU-T Study Group (SG) 13, the lead study group on the GII, and other standards organizations